THE INFLUENCE OF FACILITIES AND QUALITY OF SERVICES OF THE NAVAL HEALTH INSTITUTIONS ON PATIENT SATISFACTION IN DRS. MED.R. RIJADI SASTROPANOLA - Nugroho, Sukmo Hadi; Wahyudi, Rahmad Johan; Fendiawan, Riko (JOURNAL ASRO, 2023)
Institute Indonesian Navy Marine Health Drs. Med. R. Rijadi Sastropanola., Phys (Lakesla) is a health institution under the Indonesian Navy Health Service, as a Center of Excellence for Maritime Health with the mission of carrying out education, research, and development in the field of diving and hyperbaric health. Apart from that, Lakesla has the task of providing Oxygen Therapy services Hyperbarics (TOHB) for Indonesian Navy personnel and their families as well as the general public, both to treat cases of diving-related illnesses and clinical illnesses. With the decreasing number of patients implementing TOHB, hospitals/institutions must know how to improve their performance so that patient satisfaction can be realized and increased. Based on this problem, research is needed to find out how the facilities and service quality of the Indonesian Navy's Maritime Health Institutions influence patient satisfaction. The method used in this research is Structural Equation Modeling (SEM). In this research there are three main variables, namely: The Facilities Variable (X) consists of 6 indicators, namely: spatial considerations/planning, room planning, equipment/furniture, lighting and color, graphic messages and supporting elements. The Service Quality variable (Z) consists of 5 indicators, namely: reliability, responsiveness, assurance, empathy and tangible. Patient Satisfaction Variable (Y) which consists of 5 indicators, namely: Service, ease of getting a product or service, emotional, price and location. The conclusions obtained from this research are as follows: (1) There is a significant positive direct effect of facilities on patient satisfaction at Lakesla of 0.175. (2) There is a significant positive effect of service quality on patient satisfaction at Lakesla of 0.626. (3) There is a significant positive effect of facilities on the quality of patient service at Lakesla of 0.296. (4) There is a significant positive indirect effect of facilities through service quality (as a mediating variable) on patient satisfaction at Lakesla of 0.186. (3) There is a significant positive effect of facilities on the quality of patient service at Lakesla of 0.296. (4) There is a significant positive indirect effect of facilities through service quality (as a mediating variable) on patient satisfaction at Lakesla of 0.186. (3) There is a significant positive effect of facilities on the quality of patient service at Lakesla of 0.296. (4) There is a significant positive indirect effect of facilities through service quality (as a mediating variable) on patient satisfaction at Lakesla of 0.186. Keywords: Service Quality, Patient Satisfaction, Structural Equation Modeling (SEM)